The Role of Osteopontin and Its Gene on Glucocorticoid Response in Myasthenia Gravis - Yanchen Xie; Yanchen Xie; Hai-Feng Li; Liang Sun; Linda L. Kusner; Linda L. Kusner; Shuhui Wang; Yunxiao Meng; Xu Zhang; Yu Hong; Xiang Gao; Yao Li; et al. (Frontiers in Neurology, 2017)
Biomarkers that assess treatment response for patients with the autoimmune disorder, myasthenia gravis (MG), have not been evaluated to a significant extent. We hypothesized the pro-inflammatory cytokine, osteopontin (OPN), may be associated with variability of response to glucocorticoids (GCs) in patients with MG. A cohort of 250 MG patients treated with standardized protocol of GCs was recruited, and plasma OPN and polymorphisms of its gene, secreted phosphoprotein 1 (SPP1), were evaluated. Mean OPN levels were higher in patients compared to healthy controls. Carriers of rs11728697*T allele (allele definition: one of two or more alternative forms of a gene) were more frequent in the poorly GC responsive group compared to the GC responsive group indicating an association of rs11728697*T allele with GC non-responsiveness. One risk haplotype (AGTACT) was identified associated with GC non-responsiveness compared with GC responsive MG group. Genetic variations of SPP1 were found associated with the response to GC among MG patients.